2020
DOI: 10.21037/jtd.2020.02.23
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tobacco control interventions on smoking initiation, cessation, and prevalence: a systematic review

Abstract: This article investigates the effects of tobacco control policies on smoking initiation, cessation and prevalence by examining the papers published in the last 5 years. Twenty-one articles have been selected by two authors and sorted by four types of tobacco control: tobacco prices, anti-smoking campaigns for young people, mass media intervention and public smoking bans. Price/tax increase has deterrent effect on smoking initiation but does not promote smoking cessation; intervention on young people could redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 75 publications
1
23
0
Order By: Relevance
“…For example, for preventing cardiovascular disease, and just looking at one determinant (smoking), interventions range from psychological support to quit smoking to tobacco taxes, regulated advertising, and smoking bans in public spaces. Only when they were combined was a large impact realised [ 78 , 79 ]. The MSS is an example of a successful intervention at the individual level, but it is unlikely to have a large impact if it is not combined with a) other interventions at that level to target other determinants and b) interventions at other levels to target distress and other determinants.…”
Section: Public Mental Health Prevention To Tackle Individual and mentioning
confidence: 99%
“…For example, for preventing cardiovascular disease, and just looking at one determinant (smoking), interventions range from psychological support to quit smoking to tobacco taxes, regulated advertising, and smoking bans in public spaces. Only when they were combined was a large impact realised [ 78 , 79 ]. The MSS is an example of a successful intervention at the individual level, but it is unlikely to have a large impact if it is not combined with a) other interventions at that level to target other determinants and b) interventions at other levels to target distress and other determinants.…”
Section: Public Mental Health Prevention To Tackle Individual and mentioning
confidence: 99%
“…However, the metaanalysis research in East Africa has concluded that attitude was significantly affected by smoking behavior, and thus modifying attitude is prominent to decline smoking behavior (Tezera & Endalamaw, 2019). Attitudes and beliefs, as well as community responses about smoking also affected people to considerably quit smoking (Bafunno et al, 2020;Borrelli, Hayes, Dunsiger, & Fava, 2010;Notoatmodjo, 2005). Attitude was significantly correlated with smoking behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the most effective approaches for reducing tobacco use involve the implementation of specific excise taxes (i.e., based on quantity or weight) or ad valorem excise taxes (i.e., based on a percentage of the value of the product) which increase the retail price of tobacco [7][8][9][10]. While excise taxes have been found to delay onset of smoking, they appear to be less effective at promoting cessation among existing smokers, and particularly among heavy smokers [11][12][13]. Evidence for equity impacts (i.e., whether an intervention has a greater impact on individuals of lower or higher socioeconomic groups) of supply-side interventions is also mixed [14].…”
Section: Introduction 1tobacco Use and Controlmentioning
confidence: 99%
“…By complement, many approaches have also been used to reduce the demand for tobacco products. These include mass media campaigns, the creation of smoke-free environments, tobacco cessation services, and the adoption of cessation aids [13]. Some effective demand-side approaches include group behavioral therapy, Nicotine Replacement Therapy (NRT) and medication, and counselling interventions [16].…”
Section: Introduction 1tobacco Use and Controlmentioning
confidence: 99%
See 1 more Smart Citation